2017
DOI: 10.1007/s11064-017-2338-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PTEN Attenuates Endoplasmic Reticulum Stress and Apoptosis via Activation of PI3K/AKT Pathway in Alzheimer’s Disease

Abstract: Amyloid plaques and neurofibrillary tangles are pathologic hallmarks of Alzheimer's disease (AD). Endoplasmic reticulum (ER) stress has been implicated in the loss of neurons in AD. The phosphatase and tensin homolog deleted on chromosome ten (PTEN) plays an important role in regulating neuronal survival processes. However, the direct effects of the PTEN on ER stress and apoptosis in AD have not been elucidated. In this study, we demonstrate that the expression of PTEN and ER stress related proteins, GRP78 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 47 publications
3
47
3
Order By: Relevance
“…Further, PTEN is a lipid and protein phosphatase that inhibits PI3/AKT signaling and inhibiting PTEN has neuroprotective effects in an AD mouse model, amyloid-β toxicity, a PD model, and lab models of spinal muscular atrophy [ 95 ]. PTEN inhibition has also been shown to reduce apoptosis and counteract ER-stress related proteins in an AD mouse model [ 96 ]. In contrast, however, PTEN overexpression seems to be neuroprotective in tauopathies [ 97 ].…”
Section: Dusps In Protein Aggregation Diseasesmentioning
confidence: 99%
“…Further, PTEN is a lipid and protein phosphatase that inhibits PI3/AKT signaling and inhibiting PTEN has neuroprotective effects in an AD mouse model, amyloid-β toxicity, a PD model, and lab models of spinal muscular atrophy [ 95 ]. PTEN inhibition has also been shown to reduce apoptosis and counteract ER-stress related proteins in an AD mouse model [ 96 ]. In contrast, however, PTEN overexpression seems to be neuroprotective in tauopathies [ 97 ].…”
Section: Dusps In Protein Aggregation Diseasesmentioning
confidence: 99%
“…A study by Ling et al [30] has indicated that PI3K is a direct target of miR-320, and miR-320 could regulate the insulinresistant in 3T3-L1 adipocytes by targeting PI3K. Another study by Cui et al [47] reported that activation of PI3K/AKT signaling pathway attenuated ERs in Alzheimerʼs disease. Therefore, we suspect that miR-320 may promote ERs by directly regulation of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease ↑ GRP78 Aβ-treated SK-N-SH cells [203], RBE4 cells [204], Aβ 1-40 -treated RBE4 cells [205], Aβ 1-42 -treated bEnd.3 cells [206], 5XFAD mouse model [207], APP/PS1 transgenic mice [208], Aβ 1-42 -treated rat astrocytes, 3xTg-AD mice [209], mutant PS1 cells, 3xTg-AD mice [210]. ↓ GRP78 PS1 mutant SK-N-SH cells [211].…”
Section: Neurodegenerative Disease Upr Markers Experimental Modelmentioning
confidence: 99%
“…↑ CHOP Aβ-treated SK-N-SH cells [203], primary rat cortical neurons [212], RBE4 cells [204], temporal cortex of human AD brains [221], Aβ 1-40 -treated RBE4 cell line [205], Aβ 1-42 -treated bEnd.3 cells [206], 5XFAD mouse model [207], APP/PS1 transgenic mice [208]. ↑ GADD34 J20 mice [222], AD mouse model, human AD brains [223].…”
Section: Neurodegenerative Disease Upr Markers Experimental Modelmentioning
confidence: 99%